Comparative analysis of the expression of proliferating cell nuclear antigen, p53, bax, and bcl-2 in oral lichen planus and oral squamous cell carcinoma - Cervantes Garcia de Sousa, Fernando Augusto [UNESP]; Paradella, Thais Cachute [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Blumer Rosa, Luiz Eduardo [UNESP] (Elsevier B.V., 2009)
Several epidermiologic studies have shown the malignant transformation potential of oral lichen planus; however, this potential is subject of much controversy. To evaluate the expression of proteins related to the cell proliferation and apoptosis processes in oral lichen planus, we compared oral lichen planus with oral squamous cell carcinoma. Twenty-four cases of each lesion were submitted according to streptavidin-biotin technique to evaluate the immunohistochemical expression of proliferating cell nuclear antigen, p53, bax, and bcl-2 proteins. X 2 test showed no statistically significant differences between the expression of p53, bax, and bcl-2 in oral lichen planus and oral squamous cell carcinoma (P > .05). However, the expression of proliferating cell nuclear antigen was significantly lower in oral lichen planus than in oral squamous cell carcinoma (P < .05). No statistically significant differences between the expression of p53, bax, and bcl-2 in oral lichen planus and oral squamous cell carcinoma were observed, which may be an evidence of the potential of malignant transformation of oral lichen planus. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Lichen planus; Squamous cell carcinoma; Immunohistochemistry